2023
DOI: 10.3390/jcm12051991
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association between the Levels of Plasma Lipids and the Risk of Aortic Aneurysm and Aortic Dissection: A Two-Sample Mendelian Randomization Study

Abstract: Although a growing number of studies have attempted to uncover the relationship between plasma lipids and the risk of aortic aneurysm (AA), it remains controversial. Meanwhile, the relationship between plasma lipids and the risk of aortic dissection (AD) has not been reported on. We conducted a two-sample Mendelian randomization (MR) analysis to evaluate the potential relationship between genetically predicted plasma levels of lipids and the risk of AA and AD. Summary data on the relationship between genetic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…To investigate the speci c mechanism of aortic dissection occurrence, we further explored the mechanistic changes in the mouse aorta. Since elevated triglycerides in vivo are positively correlated with the development of aortic aneurysms [34], we rst explored lysosomal acid lipase (LAL), which is associated with TG production.…”
Section: Elevated Triglycerides Increase the Bapn-induced Scorched De...mentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the speci c mechanism of aortic dissection occurrence, we further explored the mechanistic changes in the mouse aorta. Since elevated triglycerides in vivo are positively correlated with the development of aortic aneurysms [34], we rst explored lysosomal acid lipase (LAL), which is associated with TG production.…”
Section: Elevated Triglycerides Increase the Bapn-induced Scorched De...mentioning
confidence: 99%
“…Abnormalities in lipid metabolism are associated with atherosclerosis [30,31], which is one of the risk factors for aortic dissection [32]; therefore, it is reasonable to suspect that the development of aortic dissection may be related to abnormalities in lipid metabolism. There have been articles concerning the association of abnormal lipid metabolism with aortic dissection [33,34], but none of these associations have been studied in depth. In this study, lipid metabolomics and transcriptome sequencing revealed that speci c triglycerides (TGs) were elevated speci cally in TAAD serum and that the differential lipids were associated with an in ammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Increased concentrations of non-esterified FAs induce endoplasmic reticulum stress, mitochondrial dysfunction, inflammation and cytokine release, which are causative factors of AD [93]. Observational studies found obvious dyslipidemia in AD patients, and the in-hospital mortality of AD patients was correlated with dyslipidemia [94]. The secretion of arachidonic acid (ARA) and increased synthesis of prostaglandin E2 (PGE2) are associated with endothelial dysfunction and vascular inflammation in patients with MFS [95,96].…”
Section: Lipid Metabolismmentioning
confidence: 99%